Authentication and adulteration detection of peanut oils of three flavor types using synchronous fluorescence spectroscopy. Issue 26 (21st June 2018) - Huyan, Zongyao; Ding, Shaoxuan; Liu, Xiaoli; Yu, Xiuzhu
Abstract : The fluorescence spectral region at 400–500 nm ascribed to polar compounds can be used to detect the adulteration of peanut oil of three flavors. Abstract : This study proposes a method to differentiate commercial peanut oils of various flavor types. Synchronous fluorescence spectroscopy (SyFS) associated with principal component analysis (PCA) and cluster analysis was employed to distinguish eight peanut oils from three flavor types and SyFS spectra were visualized using PCA and performed using linear discriminant analysis (LDA) to differentiate peanut oils adulterated with other vegetable oils. The tocopherol content, fatty acid composition and volatile compounds in the peanut oils were determined. The results showed that polar fluorescent compounds including various volatile compounds could be ascribed to the spectral region 400–500 nm. This region categorized the peanut oils into three categories which were the same as those for the clusters based on volatile compounds. An adulterate model using the region 400–500 nm was established. The recognition rate of LDA was 95.0%. The results demonstrated that SyFS is a feasible technique to classify and authenticate peanut oils of various flavor types.